ENERGY AND EXERGY THERMODYNAMIC ANALYSIS OF A TWO-STAGE COMPRESSION REFRIGERATION SYSTEM INTEGRATED WITH AN ABSORPTION SYSTEM (NH3+H2O) - Correa, G. A.; Souza, J. A.; Prentice-Hernández, C.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2008)
This work proposes an energetic and exergetic thermodynamic analysis of two refrigeration systems: one is a conventional two stages cooling system by steam compression of ammonia and the other is named integrated refrigeration system. The conventional system, used as reference, is largely employed in cooling fish industry. The integrated refrigeration system is similar to the conventional one, although it uses in the intermediate cooling, between the stages of high and low pressure, cold water in closed circuit. The cold water is supplied by ammonia-water absorption system integrated to the conventional compression system. The calorific energy supplied is obtained from waste exceeding of the fish meal production thus the energy delivered to the integrated refrigeration system is considered of zero cost. Numeric simulation is employed to compare the behavior of both systems. The results obtained in this comparison show that the integrated refrigeration system operates with a reduction of up to 19.73 % in COP. However, the integrated refrigeration system presented an increase of up to 25.57% in exergetic efficiency and 33.09% in frigorific capacity in relation to the conventional system. These results, added to the decrease of operational cost which will be quantified in a further study, will make very attractive the use of the integrated refrigeration system.